Saliva and Salivary Diagnostics 2019
DOI: 10.5772/intechopen.84722
|View full text |Cite
|
Sign up to set email alerts
|

Salivary Diagnostics

Abstract: Saliva is one of the most ideal diagnostic tools. It is inexpensive, noninvasive, and easy to use. Other advantages like ease of collection and minimal patient discomfort make it more acceptable to the patient as well as the clinician. The most challenging aspect in salivary diagnostics is to identify the biomarker that is linked to a disease. Researches are also ongoing to develop a device that can have reliable and valid clinical applications. This chapter briefly discusses the background and current scope o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Human saliva composition was proven by numerous past studies that it can provide information to many clinical, experimental and diagnostic protocols (Michalke et al, 2014); (Pfaffe et al, 2011) while urine has the ability to reflect systemic nickel levels in human due to its metabolic route is through the kidneys (Daniel et al, 2018); (Guo et al, 2014). Both saliva and urine are considered more tolerable to subjects because they are non-invasive techniques, accessible, convenient, and require simpler handling and sample preparation (Jayachandran et al, 2020); (Pathiyil et al, 2019); (Wang et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Human saliva composition was proven by numerous past studies that it can provide information to many clinical, experimental and diagnostic protocols (Michalke et al, 2014); (Pfaffe et al, 2011) while urine has the ability to reflect systemic nickel levels in human due to its metabolic route is through the kidneys (Daniel et al, 2018); (Guo et al, 2014). Both saliva and urine are considered more tolerable to subjects because they are non-invasive techniques, accessible, convenient, and require simpler handling and sample preparation (Jayachandran et al, 2020); (Pathiyil et al, 2019); (Wang et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Human saliva composition was proven by numerous past studies that it can provide information to many clinical, experimental and diagnostic protocols (Michalke et al, 2014;Pfaffe et al, 2011) while urine has the ability to reflect systemic nickel levels in human due to its metabolic route is through the kidneys (Guo et al, 2014, Holm et al, 2016. Both saliva and urine are considered more tolerable to subjects because they are noninvasive techniques, accessible, convenient, and require simpler handling and sample preparation (Jayachandran et al, 2020;Pathiyil et al, 2019;Wang et al, 2015). Khlifi et al reported that there was no significant difference in blood nickel level for men and women (Khlifi et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Although the collection procedures are easy and not painful, saliva composition is affected by several variables, arising from variation of salivary flow rate, circadian rhythm, type of salivary stimulus, diet, age, physiological status, and methods of collection [ 61 , 62 ]. Another reason for the limited use of saliva diagnostics is the fact that levels of most biomarkers are lower in saliva than those found in serum [ 63 ]. Advances in analytical techniques are expected to make it feasible to measure multiple biomarkers using small volumes of biological fluids including saliva.…”
Section: Discussionmentioning
confidence: 99%